HIV burden and correlates of infection among transfeminine persons and cisgender men who have sex with men in Nairobi: an observational study - Smith, A; Kimani, J; Kabuti, R; Weatherburn, P; Fearon, E; Bourne, A (Elsevier, 2021)
Background: Globally transgender persons are disproportionately affected by HIV and other sexually transmitted infections (STIs), and culturally competent prevention and treatment services are often unavailable or inaccessible. Despite recent improvements in national HIV responses for many key populations in East Africa, evidence of transgender sexual health needs to inform effective responses is sparse. We aimed to assess gender identity among men and transgender persons who have sex with men in Nairobi and explore associations with sexual health related outcomes, risk behaviour and uptake of HIV interventions.